Analisis Kepercayaan Masyarakat dalam Proses Pengambilan Keputusan Menyalurkan Zakat di Lembaga Amil Zakat Dompet Al-Qur’an - Ula, Barokatur Rizkiyatul; Salsabilla, Faizah Qonita; Maransyah, Allif Vega Putra; Ilham, Moh. (Journal of Sharia Economy and Islamic Tourism, 2024)
Trust is a feeling of "security" that arises from a person's heart based on feedback from other people. Strong trust is a determinant for being stable in making decisions. This research applies qualitative research methods and uses a case study approach. The data sources used are primary and secondary data sources, with data collection techniques in the form of interviews, observation, documentation and previous studies. This research aims to determine consumer behavior in the realm of trust in paying zakat at zakat amil institutions. The sources for this study are employees of Dompet Al-Qur'an and the surrounding community. The total number of speakers was 13 people, including 4 employees and 9 members of the public. The central location of the Al-Qur'an Wallet is at Ruko Citra City, Sari Rogo, Sidoarjo, East Java. After conducting research and analysis using the POAC theory (Planning, Organizing, Actuating, Controlling), the research results show that the planning theory in planning marketing strategies, organizing in dividing tasks, actuating in carrying out tasks, as well as controlling theory in monitoring employee work, can be realized successfully. Good. Therefore, applying POAC theory well will really bring good to the institution, because it has a direct impact on customers.